2012
DOI: 10.3109/13880209.2012.700718
|View full text |Cite
|
Sign up to set email alerts
|

Borneol alleviates oxidative stress via upregulation of Nrf2 and Bcl-2 in SH-SY5Y cells

Abstract: Borneol protected SH-SY5Y cells against Aβ-induced toxicity, exerted an antioxidative effect and suppressed apoptosis. It increases our knowledge about neuroprotective mechanism of borneol, and it is hopeful to be a candidate compound for developing therapeutic drug for the prevention and treatment of AD and other Aβ-related neurodegenerative diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 29 publications
3
25
0
2
Order By: Relevance
“…An extract of Ginkgo biloba attenuated ATP deficits and decreased oxidative damage following chemically-induced mitochondrial damage in PC12 neuronal cells [44], and stabilized mitochondrial function against nitrosative stress in primary neurons [45]. In SH-SY5Y cells, xanthoceraside, a compound extracted from Chinese flowering chestnuts, prevented Aβ-induced ROS generation, calcium overload and mitochondrial dysfunction [41] and borneol, found in many plants including wormwood and sagebrush, also decreased Aβ-induced ROS production by activating NFE2L2 [46]. …”
Section: Discussionmentioning
confidence: 99%
“…An extract of Ginkgo biloba attenuated ATP deficits and decreased oxidative damage following chemically-induced mitochondrial damage in PC12 neuronal cells [44], and stabilized mitochondrial function against nitrosative stress in primary neurons [45]. In SH-SY5Y cells, xanthoceraside, a compound extracted from Chinese flowering chestnuts, prevented Aβ-induced ROS generation, calcium overload and mitochondrial dysfunction [41] and borneol, found in many plants including wormwood and sagebrush, also decreased Aβ-induced ROS production by activating NFE2L2 [46]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that borneol has free radical scavenging activity (95) and is a major component of essential oil of SuHeXiang Wan (92) whose neuroprotective function has been reported in in vivo and in vitro models of Alzheimer’s disease (AD) (9699). Moreover, a recent study showed that borneol exerts a neuroprotective effect against β-amyloid (Aβ) cytotoxicity via upregulation of nuclear translocation of Nrf2 and expression of Bcl-2 (100). In addition, treatment with isoborneol, a monoterpenoid alcohol, significantly reduced 6-hydroxydopamine-induced ROS generation and cell death in human neuroblastoma SH-SY5Y cells, suggesting that isoborneol may be a potential therapeutic agent for treatment of neurodegenerative diseases associated with oxidative stress (101).…”
Section: Terpenes and Neuronal Healthmentioning
confidence: 99%
“…For example, neuronsKarkkainen et al, 2014). In addition, the ability of Nrf2 to upregulate the expression of anti-oxidant genes 720 via ARE suggests that increasing Nrf2 activity may pro-721 vide a useful system for combating oxidative insults.Several recent reports have demonstrated that coordi-723 nated upregulation of ARE-driven genes protects SH-SY5Y cells from Ab-induced neurotoxicity(Lee et al, 725 2011;Wang et al, 2012;Hur et al, 2013).Nrf2-activating compounds, the usefulness of these mole-731 cules in disease is unclear due to a lack of information 732 regarding their ability to enter the central nervous system. Thus, in the search for compounds that activate Nrf2 sig-…”
mentioning
confidence: 98%